Fundamentals of accountancy, business, and management 1 - Camerino, Danilo S. (Makati City : Diwa Learning Systems, Inc., 2020)
"Basic knowledge of accountancy is an advantage regardless of which field you eventually pursue in your studies. It bears practical significance as it places you in a position to better handle your finances to serve your best purposes. The goal of this book is to provide you with basic knowledge of how financial records are managed and how business decisions and transactions impact the financial health of an organization. The actual practices and applications that you will go through will give you a better appreciation of good accounting and financial management".
Includes bibliography.
Keywords: Business; Management; Accounting